OPTIMIZATION OF TEMPERATURE HARDENING FOR IMPROVING THE HEAT RESISTANCE OF TOOL STEEL 4X5MФ1С IN VARIOUS WORKPIECES Part 1. INFLUENCE OF HEATING TEMPERATURE 1040 °С IN THE OIL HARDENING AND HARDERING ON THE HARDNESS AND STRUCTURE OF FORGINGS AND CASTINGS MADE OF STEEL 4X5MФ1C - V. N. Fedulov (Литьë и металлургия, 2017)
Influence of the oil quenching temperature with the heating 1040 °С near 1 hour of tool steel 4X5МФ1С forgings and castings on the microstructure and the ability to hardening after high temperature tempering at 500–650 °C for 1, 5 hours. It was shown that increase of hardening level in comparison with the required index has not been achieved.